Circular antiviral RNA - Omar, Abdul Rahman; Tejo, Bimo Ario; Tan, Sheau Wei; Choong, Oi Kuan (2012)
The present invention relates to triple helix forming oligonucleotides (TFO) for use in the treatment of diseases mediated by single stranded RNA viruses, for example corona viruses. The invention provides a selection of circular TFO sequences that target different regions of the genome of the virulent Feline coronavirus and that efficiently block the virus’ replication. Thereby the TFO of the present invention provide new means for therapy against viral diseases. The invention relates to the novel TFOs, pharmaceutical compositions comprising the same, the new TFO design and their uses in the treatment of viral diseases.